A rapid preparation method of charged lunar dust protection thermal control structure suitable for large-area application
Patent Information
- Application Number
- CN202510450173.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-11
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-04-11
AI Technical Summary
[0005]本发明为了解决现有热控涂层由于月尘影响引起热控性能迅速下降问题,提供一种带电月尘防护热控涂层及其制备方法和应用
[0021]本发明首先通过在掺杂导电粒子实现热控涂层的导电,然后通过低表面能的氟聚氨酯作为粘结剂与填料粒子纳米二氧化硅在热控涂层表面构筑出适宜尺寸的微观结构,并利用低表面能的氟聚氨酯对涂层表面进行改性,获得月尘防护热控涂层。本发明以氟聚氨酯作为粘结剂,纳米二氧化硅为填料,通过喷涂法即可制备获得月尘防护热控涂层,避免了表面改性的多步复杂工艺,易于大面积应用。且填料粒子纳米二氧化硅在热控涂层表面构筑出月尘防护所需微观结构,降低了涂层与月尘之间的范德华力,且喷涂后的热控涂层仍然具有良好的体电阻率,降低了静电黏附,实现了带电月尘的防护。同时纳米SiO2与氟聚氨酯都有良好的空间稳定性,适应月表极端环境。
Smart Images

Figure CN120286323B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a rapid preparation method for a charged lunar dust protection thermal control structure suitable for large-area applications, belonging to the field of functional material preparation technology. Background Technology
[0002] Thermal control coatings are coatings on the surface of spacecraft that control and regulate the reflection of sunlight and infrared emissivity to maintain the internal operating temperature balance of the spacecraft. They are crucial components for achieving thermal control of spacecraft. The lunar surface, due to meteorite impacts and long-term weathering, has formed a layer of small, irregularly shaped lunar dust particles. Simultaneously, long-term exposure to space radiation has resulted in the lunar dust surface being richly charged. During lunar exploration, these lunar dust particles, due to their small size, large specific surface area, and low surface energy, easily adhere to the lunar rover surface, causing a decline in thermal control performance, leading to thermal imbalance and damage to the spacecraft's internal structure. Therefore, there is an urgent need to develop a thermal control coating that protects against charged lunar dust. This coating must meet the following requirements: First, it must have a low solar absorptivity and a high infrared emissivity to ensure efficient thermal control performance; second, it must have a low-surface-energy surface with a suitable microstructure to reduce lunar dust adhesion caused by van der Waals forces; and finally, it must have a suitable volume resistivity to reduce electrostatic adhesion of lunar dust.
[0003] Currently, there are many types of thermal control coatings, mainly including secondary surface mirrors, ceramic protective materials, and thermal control white paints. Among them, thermal control white paints are widely used on the surfaces of various spacecraft due to their simple preparation process, ease of large-area spraying, good designability, and excellent thermal control performance. Organic thermal control white paints are increasingly widely used in spacecraft due to their lightweight and good adhesion. Conductive thermal control white paints are mainly composed of organic binders, conductive fillers, and white fillers. In space environment applications, thermal control white paints must have a certain degree of conductivity to cope with the charging and discharging effects of the space environment. A common method of conductivity is through the conductive modification of nanoparticles, thereby giving the thermal control coating a relatively low volume resistivity. The low volume resistivity of the thermal control coating can significantly reduce the electrostatic adhesion of lunar dust.
[0004] However, lunar dust particles, widely distributed on the lunar surface, are highly susceptible to adhesion to thermal control coatings due to their small size, large specific surface area, and high surface energy. This adhesion, caused by van der Waals forces, leads to a decline in the performance of the thermal control coating. Lunar dust particle adhesion is typically caused by the combined effects of van der Waals forces and electrostatic forces. To effectively protect against lunar dust, the influence of these two forces must be reduced. To reduce van der Waals forces, appropriate surface roughness and reduced surface energy can be achieved. Thermal control coatings used in space environments often have anti-static requirements, which can significantly reduce adhesion caused by electrostatic forces. Therefore, current research on avoiding lunar dust adhesion mainly focuses on reducing van der Waals forces. To reduce lunar dust adhesion to the thermal control coating surface caused by van der Waals forces, a low surface energy surface with suitable microscale dimensions must be constructed on the thermal control coating surface. Current technologies typically utilize nanoparticles and binders to construct microstructures on the coating surface and perform low surface energy modification. However, these methods often face problems of complex processes and numerous steps, severely limiting their large-scale application. Summary of the Invention
[0005] To address the problem of rapid decline in thermal control performance caused by lunar dust in existing thermal control coatings, this invention provides a charged lunar dust protective thermal control coating, its preparation method, and its application.
[0006] The technical solution of the present invention:
[0007] One objective of this invention is to provide a method for preparing a thermally controlled protective coating against charged lunar dust, the method comprising the following steps:
[0008] (1) AZO was coated on the surface of ZrO2 using atomic layer deposition technology to obtain AZO@ZrO2 powder;
[0009] (2) Mix AZO@ZrO2 powder, fluoropolyurethane and butyl acetate evenly to obtain AZO@ZrO2 thermal control slurry. Spray the AZO@ZrO2 thermal control slurry onto the substrate surface to obtain an antistatic AZO@ZrO2 thermal control coating.
[0010] (3) Mix hydrophobic silica, fluoropolyurethane and butyl acetate evenly to obtain SiO2 hydrophobic dustproof slurry. Spray the SiO2 hydrophobic dustproof slurry onto the surface of the antistatic AZO@ZrO2 thermal control coating using the same spraying method as (2) to obtain a charged dustproof thermal control coating.
[0011] Further defined, (1) the operation process is as follows: place nano ZrO2 powder in the deposition chamber of the atomic layer deposition instrument, set the deposition pressure to 0.15 torr, the temperature to 140℃, the rotation speed of the drum deposition chamber to 600r / min, the atomic ratio of zinc to aluminum to 23:1, the spray time for each deposition growth cycle is 60s, and repeat for 48 cycles.
[0012] Further specifying, in (2), the mass-to-volume ratio of AZO@ZrO2 powder, fluoropolyurethane and butyl acetate is 20g:4g:20mL.
[0013] Further specified, (2) spraying parameters are: spray gun nozzle diameter 1.5mm, spraying atmosphere 0.3mpa high-purity nitrogen, distance between spray gun and substrate not exceeding 25cm, spraying fan-shaped area at 90° to surface, after completing one spraying, rotate substrate 90° for the next spraying, multiple sprayings to achieve target thickness, complete spraying, and finally place in oven to dry.
[0014] Furthermore, the drying temperature is specified as 60℃, and the drying time is specified as 3 hours.
[0015] Further specified, the mass-volume ratio of hydrophobic silica, fluoropolyurethane and butyl acetate in (3) is 0.2g:0.1g:20mL.
[0016] Further specifying, the particle size of the hydrophobic silica in (3) is 15 nm.
[0017] Further specifying, in (2), the substrate is a 40×40mm aluminum substrate.
[0018] The second objective of this invention is to provide a charged lunar dust protective thermal control coating prepared by the above method.
[0019] The third objective of this invention is to provide an application of the aforementioned charged lunar dust protective thermal control coating, specifically for lunar dust protection on spacecraft surfaces.
[0020] Beneficial effects:
[0021] This invention first achieves conductivity in the thermal control coating by doping with conductive particles. Then, using low-surface-energy fluoropolyurethane as a binder and nano-silica as a filler, a microstructure of suitable size is constructed on the surface of the thermal control coating. The surface of the coating is then modified using low-surface-energy fluoropolyurethane to obtain a lunar dust-protective thermal control coating. This invention uses fluoropolyurethane as a binder and nano-silica as a filler, and the lunar dust-protective thermal control coating can be prepared by spraying, avoiding the complex multi-step surface modification process and facilitating large-area application. Furthermore, the nano-silica filler constructs the microstructure required for lunar dust protection on the surface of the thermal control coating, reducing the van der Waals forces between the coating and lunar dust. The sprayed thermal control coating still maintains good volume resistivity, reducing electrostatic adhesion and achieving protection against charged lunar dust. Simultaneously, both nano-SiO2 and fluoropolyurethane exhibit good dimensional stability, adapting to the extreme environment of the lunar surface. Attached Figure Description
[0022] Figure 1 SEM images of the coating prepared in Comparative Example 1 (at different magnifications);
[0023] Figure 2 SEM images (at different magnifications) of the coating prepared in Example 1;
[0024] Figure 3 The reflectance spectra of the coatings prepared in Example 1 and Comparative Example 1 are shown.
[0025] Figure 4 The emission spectra of the coatings prepared in Example 1 and Comparative Example 1 are shown.
[0026] Figure 5 A comparison diagram of the volume resistivity of the coatings prepared in Example 1 and Comparative Example 1;
[0027] Figure 6 Dust removal angle diagrams of the coatings prepared in Example 1 and Comparative Example 1;
[0028] Figure 7 TEM image and EDS elemental distribution map of AZO@ZrO2 powder. Detailed Implementation
[0029] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0030] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0032] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials, reagents, methods, and instruments used are all conventional materials, reagents, methods, and instruments in the art, and can be obtained commercially by those skilled in the art.
[0033] Example 1:
[0034] (1) Preparation of AZO@ZrO2 powder:
[0035] 15g of ZrO2 powder with a particle size of 200nm was placed in the deposition chamber of an atomic layer deposition apparatus. The pressure in the deposition chamber was set to 0.15 torr, the temperature in the deposition chamber was set to 140℃, the rotation speed of the drum deposition chamber was set to 600r / min, the zinc-aluminum atomic ratio during deposition was 23:1, the spray time was 60s, and the atomic layer deposition growth cycle was repeated for 48 cycles to coat the ZrO2 powder with AZO, thus obtaining AZO@ZrO2 powder.
[0036] (2) Substrate pretreatment:
[0037] A 40×40mm aluminum substrate was ultrasonically cleaned sequentially with anhydrous ethanol, acetone, and anhydrous ethanol for 15 minutes each, then dried in an oven for later use.
[0038] (3) Preparation of AZO@ZrO2 thermally controlled slurry:
[0039] 4g of fluoropolyurethane was dissolved in 20mL of butyl acetate solution. 20g of AZO@ZrO2 powder was added to the solution and stirred with a magnetic stirrer for 2h to disperse it evenly, thus obtaining AZO@ZrO2 thermal control slurry.
[0040] (4) Preparation of antistatic thermal control coating:
[0041] Using a spraying device, a 1.5mm diameter spray gun was used for spraying under high-purity nitrogen at a pressure of 0.3MPa. During spraying, AZO@ZrO2 thermal control slurry was injected into the pigment cup. The substrate treated in step (2) was placed on the spraying table. The spray gun was held in hand, keeping the distance between the substrate and the sample no more than 25cm. The spray gun switch was pressed, and after stabilization, the spray gun was moved parallel to the spraying surface at a uniform speed. The spraying fan was kept at 90° to the surface. A cross-spraying method was used during the spraying process. After the sample was sprayed once, it was rotated 90° to complete the second spraying to ensure the uniformity of the spraying. After the first spraying was completed, the substrate was placed in a 60℃ oven for constant temperature drying for 3 hours before the next spraying was performed. Multiple sprayings were performed until the thickness reached 175μm, and then the spraying was stopped. After the spraying was completed, the sample was removed and placed in an oven at 60℃ for constant temperature drying for 3 hours to obtain a substrate with an antistatic AZO@ZrO2 thermal control coating.
[0042] (5) Preparation of SiO2 hydrophobic dustproof slurry:
[0043] Dissolve 0.1g of fluoropolyurethane in 20mL of butyl acetate solution, add 0.2g of 15nm hydrophobic silica to the solution, and stir with a magnetic stirrer for 2h to disperse evenly to obtain SiO2 hydrophobic dustproof slurry.
[0044] (6) Preparation of a thermal control coating for protection against charged lunar dust:
[0045] Using the same spraying method as (4), SiO2 hydrophobic dustproof slurry was sprayed onto the surface of the thermal control coating to adjust the microstructure. The spraying thickness was 1 μm, and a charged dustproof thermal control coating was prepared.
[0046] Comparative Example 1:
[0047] (1) Preparation of AZO@ZrO2 powder:
[0048] 15g of ZrO2 powder with a particle size of 200nm was placed in the deposition chamber of an atomic layer deposition apparatus. The pressure in the deposition chamber was set to 0.15 torr, the temperature in the deposition chamber was set to 140℃, the rotation speed of the drum deposition chamber was set to 600r / min, the zinc-aluminum atomic ratio during deposition was 23:1, the spray time was 60s, and the atomic layer deposition growth cycle was repeated for 48 cycles to coat the ZrO2 powder with AZO, thus obtaining AZO@ZrO2 powder.
[0049] (2) Substrate pretreatment:
[0050] A 40×40mm aluminum substrate was ultrasonically cleaned sequentially with anhydrous ethanol, acetone, and anhydrous ethanol for 15 minutes each, then dried in an oven for later use.
[0051] (3) Preparation of AZO@ZrO2 thermally controlled slurry:
[0052] 4g of fluoropolyurethane was dissolved in 20mL of butyl acetate solution. 20g of AZO@ZrO2 powder was added to the solution and stirred with a magnetic stirrer for 2h to disperse it evenly, thus obtaining AZO@ZrO2 thermal control slurry.
[0053] (4) Preparation of antistatic thermal control coating
[0054] Using a spraying device, a 1.5mm nozzle spray gun was used to spray under high-purity nitrogen at a pressure of 0.3MPa. During spraying, AZO@ZrO2 thermal control slurry was injected into the pigment cup. The substrate treated in step (2) was placed on the spraying table. The spray gun was held in hand, keeping the distance between the substrate and the sample no more than 25cm. The spray gun switch was pressed, and after stabilization, it was moved parallel to the spraying surface at a uniform speed. The spraying fan was kept at 90° to the surface. A cross-spraying method was used during the spraying process. After the sample was sprayed once, it was rotated 90° to complete the second spraying to ensure the uniformity of the spraying. After the first spraying was completed, the substrate was placed in a 60℃ oven for constant temperature drying for 3 hours before the next spraying was performed. Multiple sprayings were performed until the thickness reached 175μm, and then the spraying was stopped. After the spraying was completed, the sample was removed and placed in an oven at 60℃ for constant temperature drying for 3 hours to obtain an antistatic AZO@ZrO2 thermal control coating.
[0055] Comparative Example 2:
[0056] The difference between this comparative example and Example 1 is that ZrO2 powder is used to replace AZO@ZrO2 powder in (3), while the remaining process steps and parameter settings are the same as in Example 1.
[0057] Example of effect:
[0058] (1) Figure 7 The images shown are TEM images and EDS elemental distribution maps of the AZO@ZrO2 powder prepared in Example 1. Figure 1 It can be seen that AZO can completely coat zirconium dioxide, forming an AZO@ZrO2 core-shell structure, with an AZO shell thickness of approximately 5.3 nm. Furthermore, the EDS elemental distribution results show that the AZO@ZrO2 powder contains four elements: Zr, O, Zn, and Al, with Zn and Al being uniformly distributed. This indicates that an AZO conductive layer has been successfully and uniformly deposited on the surface of ZrO2 particles via ALD.
[0059] (2) Figure 1 and Figure 2The images show SEM images of the antistatic AZO@ZrO2 thermal control coating prepared in Comparative Example 1 and the charged lunar dust protective thermal control coating prepared in Example 1 at different magnifications. As can be seen from the images, the surface of the antistatic AZO@ZrO2 thermal control coating exhibits micron-sized pores and protrusions. These micron-sized pores and protrusions easily allow lunar dust particles to become trapped in the pores, causing lunar dust adhesion, which is detrimental to the dust-proof properties of the thermal control coating. In contrast, the micron-sized pores and protrusions on the surface of the charged lunar dust protective thermal control coating prepared in Example 1 are smoothed out, effectively preventing lunar dust particles from becoming trapped in the pores and causing lunar dust adhesion. Under high-magnification scanning electron microscopy, it can be observed that the original submicron-sized protrusions on the surface of the thermal control coating have completely disappeared, replaced by a dense nanostructure. These nanoscale protrusions significantly reduce the contact area when the coating comes into contact with lunar dust, effectively reducing van der Waals forces.
[0060] (3) The absorbance in the 200-2500 nm wavelength range and the emissivity in the 2-16 μm wavelength range of the antistatic AZO@ZrO2 thermal control coating prepared in Comparative Example 1 and the charged dust-protective thermal control coating prepared in Example 1 were compared using ultraviolet-visible-near-infrared spectroscopy and Fourier transform infrared spectroscopy, respectively. This verified the influence of the hydrophobic dust-proof layer on the thermal control performance of the coating. The results are as follows: Figure 3 and Figure 4 As shown in the figure, in the 200-2500nm wavelength range, the absorptivity of Experimental Example 1 is 0.125, and that of Comparative Example 2 is 0.123. This indicates that the absorptivity does not change much after spraying a hydrophobic and dustproof layer on the surface of the antistatic AZO@ZrO2 thermal control coating, and it still maintains good reflectivity in the near-ultraviolet and far-infrared bands.
[0061] Analysis of emission performance showed that in the 2-16μm band, the emissivity of Experimental Example 1 was 0.923 and that of Comparative Example 1 was 0.919, indicating that the emissivity did not change much after spraying a hydrophobic and dustproof layer on the surface of the antistatic AZO@ZrO2 thermal control coating.
[0062] In summary, the hydrophobic and dust-proof modification of the AZO@ZrO2 thermal control coating did not significantly alter its thermal control performance.
[0063] (4) The volume resistivity of the coating was measured using a high-resistivity microcurrent tester. The volume resistivity of Experiment 1 was 4.5 × 10⁻⁶. 6 The volume resistivity of Comparative Example 1 is 3.5 × 10 Ω·m. 6 After constructing the surface microstructure using nano-silica, the volume resistivity did not decrease significantly, still meeting the international standard for volume resistivity of antistatic thermal control coatings. In contrast, the resistivity of Comparative Example 2 was 9.2 × 10⁻⁶ Ω·m. 12The value of Ω·m indicates that the volume resistivity of the coating decreased significantly after modification with AZO-coated powder, and the modified coating meets the international standard for volume resistivity of antistatic thermal control coatings.
[0064] (5) The dustproof performance of the antistatic AZO@ZrO2 thermal control coating prepared in Comparative Example 1 and the charged lunar dust protective thermal control coating prepared in Example 1 was tested using lunar dust. The coatings were placed horizontally, and charged lunar dust was sprayed onto the coating surface using an electrostatic powder sprayer. The sample was then slowly tilted, allowing the charged lunar dust to slide off naturally under gravity. The tilt angle at which the lunar dust slid off was recorded. The test results are as follows: Figure 6 As shown, by Figure 6 It can be seen that the average dust removal angle of the coating prepared in Experimental Example 1 is 52°, while the average dust removal angle of the coating prepared in Comparative Example 1 for charged lunar dust is 65°. This indicates that after antistatic modification, the coating surface has a significantly improved ability to protect against charged lunar dust.
[0065] The above description is only a preferred embodiment of the present invention. Given that those skilled in the art can make appropriate changes and modifications to the above embodiments, the present invention is not limited to the specific embodiments described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention.
Claims
1. A rapid preparation method for a charged lunar dust protective thermal control structure suitable for large-area applications, characterized in that, include: (1) AZO was coated on the surface of ZrO2 using atomic layer deposition technology to obtain AZO@ZrO2 powder; (2) Mix AZO@ZrO2 powder, fluoropolyurethane and butyl acetate evenly to obtain AZO@ZrO2 thermal control slurry. Spray the AZO@ZrO2 thermal control slurry onto the substrate surface to obtain an antistatic AZO@ZrO2 thermal control coating. (3) Mix hydrophobic silica, fluoropolyurethane and butyl acetate evenly to obtain SiO2 hydrophobic dustproof slurry. Spray the SiO2 hydrophobic dustproof slurry onto the surface of the antistatic AZO@ZrO2 thermal control coating using the same spraying method as (2) to obtain a charged dustproof thermal control coating.
2. The preparation method according to claim 1, characterized in that, (1) The operation process is as follows: ZrO2 powder with a particle size of 200 nanometers is placed in the deposition chamber of the atomic layer deposition instrument, the deposition pressure is set to 0.15 torr, the temperature is 140℃, the rotation speed of the drum deposition chamber is 600r / min, the atomic ratio of zinc source to aluminum source is 23:1, the spraying time for each deposition growth cycle is 60s, and the cycle is repeated for 48 cycles.
3. The preparation method according to claim 1, characterized in that, (2) The mass-volume ratio of AZO@ZrO2 powder, fluoropolyurethane and butyl acetate is 20g:4g:20mL.
4. The preparation method according to claim 1, characterized in that, (2) The spraying parameters are: spray gun nozzle diameter 1.5mm, spraying atmosphere 0.3mpa high-purity nitrogen, the distance between the spray gun and the substrate does not exceed 25cm, the spraying fan is at 90° to the surface, after completing one spraying, rotate the substrate 90° for the next spraying, spray multiple times to reach the target thickness, complete the spraying, and finally place it in the oven to dry.
5. The preparation method according to claim 4, characterized in that, The drying temperature is 60℃ and the time is 3 hours.
6. The preparation method according to claim 1, characterized in that, (3) The mass-volume ratio of hydrophobic silica, fluorinated polyurethane and butyl acetate is 0.2g:0.1g:20mL.
7. The preparation method according to claim 1, characterized in that, (3) The particle size of the hydrophobic silica is 15 nm.
8. The preparation method according to claim 1, characterized in that, (2) The substrate is an aluminum substrate of 40×40mm.
9. An electrically protective thermal control coating prepared by the method according to any one of claims 1 to 8.
10. An application of the electrically protective thermal control coating as described in claim 9, characterized in that, Used for lunar dust protection on spacecraft surfaces.
